The Effect of Roflumilast on Absolute Neutrophil Count, MMP-9 Serum, % VEP1 Value, and CAT Scores in Stable COPD Patients - Ratna Adhika; Suradi Suradi; Yusup Subagio Sutanto (Jurnal Respirologi Indonesia, 2022)
Background: Chronic obstructive pulmonary disease is the leading cause morbidity and mortality worldwide. Cigarette smoke and noxious agent causing oxidative stress activated nuclear factor-κB then increase inflammatory cell releases. Roflumilast have antiiinflammatory effect which can be use as addition therapy for stable COPD.Methods: The pretest and postest experimental clinical trial was carried out in 40 patients with stable COPD in the pulmonology outpatient clinics of Dr. Moewardi Surakarta and dr. Soehadi Prijonegoro Sragen hospital from 6 January to 6 March 2020. Forty subjects were grouped into treatment group (n=20) receiving standart therapy along with roflumilast 500 mg/day and placebo group (n=20) receiving standart therapy only for 28 days. Decreased inflammation measured by ANC and serum MMP-9, improvement of obstruction measured by % FEV1, and clinic improvement measured by CAT score.Results: Our finding revealed decreases of ANC and MMP-9 serum in the treatment group, although statistically insignificant (p=0,449), (p= 0,195) respectively. %VEP1 value increased insignificant in the treatment groups (p=0,189). Chronic obstructive pulmonary disease assessment test (CAT) score decreased significantly in the treatment group (p=0.000).Conclusion: Roflumilast administration reduce inflammation as it can lower not significant ANC, MMP-9 serum, higher not significant %VEP1, and improves the clinical condition of patients with stable COPD based on a decrease in CAT score.